Neuroendocrine Breast Carcinoma: Case Report and Review of the Literature - Maha Abdel Hadi; Nosiaba Telmesani; Afnan Al Muhanna; Ayesha Ahmed; Haitham Kussaibi; Muhammad Iftikhar; Mohammad Athar Nizami; Arwa A. Nabhan (Dubai Medical Journal)
Primary breast carcinoma with neuroendocrine features is an uncommon presentation of mammary cancers. The authors present a case of a rapidly growing breast mass that raised many differential diagnoses. The diagnosis in this case was challenging. Extensive clinical assessment, radiological imaging, nuclear scans, pathological evaluations, and series of multidisciplinary meetings were utilized to reach the diagnosis of neuroendocrine breast carcinoma.